Identitas Situbondo Sebagai Kota Santri Pancasila Terhadap Pembentukan Karakter Pancasila Santri Salafiyah Syafi’iyah Sukorejo Situbondo - Dairani Dairani (Jurnal Hukum dan Sosial Politik, 2024)
The birth of Pancasila as an ideology and the foundation of the Indonesian nation and state certainly cannot be separated from the efforts and struggles of the founders of the Indonesian nation and one of the famous figures who initiated Pancasila was Soekarno who was also the first President of the Republic of Indonesia. In historical records, Soekarno stated that Pancasila was on one of the islands in the eastern region when he was exiled, namely Ende Island in NTT until finally as a reward the island was given the name Pancasila Island. Likewise with Kab. Situbondo, East Java, since November 10 2022 has been named the City of Santri Pancasila by the Regent of Situbondo as a tribute to KHR. As'ad Syamsul Arifin for his services as a pioneer in accepting the Single Principle of Pancasila since the New Order which was then followed up with the 1984 NU Congress in the Salafiyah Syafi'iyah PP in which the obligation to accept, maintain and preserve Pancasila as the basis of the state was discussed and there was no need to contradict it. This article discusses the influence of the Pancasila Santri City on the character formation of Sukorejo Salafiyah Syafi'iyah students with research results showing that there is a big influence of struggle and appreciation for KHR services. As'ad Syamsul Arifin in forming the Pancasila character of students.